Evaluation of anthropogenic emissions of black carbon from East Asia in six inventories: constraints from model simulations and surface observations on Fukue Island, Japan. Issue 3 (24th February 2022) - Ikeda, Kohei; Tanimoto, Hiroshi; Kanaya, Yugo; Taketani, Fumikazu
Abstract : This study evaluates anthropogenic black carbon emissions from East Asia for five global inventories and one regional inventory using a chemical transport model and observations at Fukue Island in Japan. Abstract : Bottom-up emission inventories of black carbon (BC) are used to assess its impact on the climate and air quality using climate models and chemical transport models. However, the estimates of BC emissions from East Asia, the region with the largest anthropogenic emissions, are still uncertain. We evaluated anthropogenic BC emissions from East Asia for five global inventories and one regional inventory using a chemical transport model, GEOS-Chem, and observations at Fukue Island in western Japan. The inventories examined in this study include REASv2.1, HTAPv2, MACCity, ECLIPSEv5a, CEDS, and EDGARv4.3.2. We first compared BC emissions in East Asia for the six inventories by source region and sector. BC emissions from China were estimated to be 1.32–2.44 Tg per year for 2010 with a large difference of 85% between the maximum (CEDS) and minimum (EDGARv4.3.2). We then conducted model simulations for the six inventories using GEOS-Chem and compared them with the observations at Fukue Island. To evaluate Chinese BC emissions, we used a tagged method to select BC data strongly affected by BC transported from China and excluded data influenced by wet scavenging during transport. The comparisons after the data selection showed that the average BC concentrations in the simulations were 25–116% larger than the observed values. We estimated BC emissions from China to be 1.14 Tg per year averaged for 2009–2011 using the ratios of simulated to observed concentrations, suggesting that CEDS used in CMIP6 and ECLIPSEv5a overestimates Chinese BC emissions. Seasonal analysis suggests that the domestic sector in winter leads to the overestimation of these inventories.